Even the Little Children Cooperated: Family Strategies, Childcare Discourse, and Social Welfare Debates 1945-1975 - Finkel, Alvin (Labour/Le Travailleur, 1995)
The debate about public funding and regulation of childcare has always had as its central focus: should mothers be encouraged or discouraged from seeking paidwork outside the home? While some scholars argue that labour needs — the"reserve army" thesis — best explain resulting public policies regarding childcare, this article argues that campaigns by women's organizations, sometimes aided by mixed-sex progressive social organizations, have been more important in public policy-making. Discourse on paid work for women with children has shifted from 1945 to 1990 from extremely negative to ambivalent. But the Right has limited the impact of women's mobilization for shared state responsibility for childcare by insisting on childcare arrangements as a working mother's responsibility.